2011
DOI: 10.1097/hjh.0b013e3283487806
|View full text |Cite
|
Sign up to set email alerts
|

In-vivo nitric oxide synthesis is reduced in obese patients with metabolic syndrome

Abstract: The advantages of the new saliva ONT method are its accuracy, sensitivity and lack of invasiveness, which could make it a reference method for the assessment of in-vivo rates of whole-body nitric oxide synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 51 publications
(71 reference statements)
4
41
0
Order By: Relevance
“…For example, it has been shown that serum nitrate and nitrite levels, an index of systemic NO bioavailability, were less in juvenile obese subjects with elevated systolic arterial pressure when compared with normal weight controls. 59 In vivo NO production, as measured by an oral nitrate test, 60 was also less in obese subjects with metabolic syndrome when compared with obese subjects without metabolic syndrome. 60 Consistent with this, we recently found that plasma nitrate and nitrite levels were less in obese hypertensive subjects when compared with their obese normotensive counterparts.…”
Section: Are No Bioavailability and L-argininementioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been shown that serum nitrate and nitrite levels, an index of systemic NO bioavailability, were less in juvenile obese subjects with elevated systolic arterial pressure when compared with normal weight controls. 59 In vivo NO production, as measured by an oral nitrate test, 60 was also less in obese subjects with metabolic syndrome when compared with obese subjects without metabolic syndrome. 60 Consistent with this, we recently found that plasma nitrate and nitrite levels were less in obese hypertensive subjects when compared with their obese normotensive counterparts.…”
Section: Are No Bioavailability and L-argininementioning
confidence: 99%
“…59 In vivo NO production, as measured by an oral nitrate test, 60 was also less in obese subjects with metabolic syndrome when compared with obese subjects without metabolic syndrome. 60 Consistent with this, we recently found that plasma nitrate and nitrite levels were less in obese hypertensive subjects when compared with their obese normotensive counterparts. 5 Furthermore, it has been demonstrated that greater systolic arterial pressure is associated with reductions in NO synthesis in obese subjects.…”
Section: Are No Bioavailability and L-argininementioning
confidence: 99%
“…Twenty minutes after glucose administration, 201 mU of Human Actrapid insulin was given. A total of 30 blood samples were taken at )10, )5, )1, 1, 2, 3, 4, 5,6,8,10,13,15,20,25,30,35,40,50,60,70,80,90, 100, 120, 140, 160, 180, 210 and 240 min relative to the administration of glucose. Insulin sensitivity (Si) was characterised by the minimal model as defined by Bergman et al [12].…”
Section: Frequent Sampling Intravenous Glucose Tolerance Test (Fsivgtt)mentioning
confidence: 99%
“…All subsequent saliva samples were collected by the volunteer at home using pre-labelled containers. The protocol for the collection of saliva samples has been previously described [8]. The final saliva sample was collected 18 h after the meal on the following morning.…”
Section: Salivary Oral Nitrate Test (S-ont)mentioning
confidence: 99%
“…41 Compounding these effects, obese individuals also have a decreased capacity for NO production. 42 NO and nitrate have well established vasodilatory properties. Therefore the increased activity of the XOR catalyzed nitrate-nitrite-NO pathway may function as an adaptive response to hypoxia in adipose tissue, especially in the setting of obesity, where it may have the tandem effect of dilating the blood vessels to improve tissue oxygenation and activating the browning process in adipocytes to reverse hypoxia-mediated pathological metabolic reprogramming (Fig.…”
mentioning
confidence: 99%